1992
DOI: 10.1128/iai.60.3.728-734.1992
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of the elastase from Aspergillus fumigatus

Abstract: Elastase, a potential virulence factor from the opportunistic pathogen Aspergillus fumigatus, was purified 220-fold from culture broth by fast-performance liquid chromatography employing anion exchange (Q Sepharose fast flow), cation exchange (S Sepharose fast flow), and gel filtration (Superose 12). Purified to near homogeneity, the elastase had an apparent molecular mass of 32 kDa by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (silver stain) but a mass of about 19.1 kDa as determined by gel fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 26 publications
5
37
0
1
Order By: Relevance
“…Interestingly, similar results have been obtained by us [33] and other workers [26,[34][35][36] using more complex procedures. The molecular mass of the purified enzyme was estimated to be between 20 and 35 kDa [35] and more precisely 32-33 kDa [26,33,34,36]; minor bands with molecular masses lower than 30 kDa were demonstrated to be self-degradation products of the enzyme [26,34,36]. Moreover, these results obtained using different strains of A. fumigatus suggest that this 32-33-kDa serine proteinase is highly conserved in this pathogen.…”
Section: Fumigatus Various Enzyme Activities Were Charac-supporting
confidence: 88%
“…Interestingly, similar results have been obtained by us [33] and other workers [26,[34][35][36] using more complex procedures. The molecular mass of the purified enzyme was estimated to be between 20 and 35 kDa [35] and more precisely 32-33 kDa [26,33,34,36]; minor bands with molecular masses lower than 30 kDa were demonstrated to be self-degradation products of the enzyme [26,34,36]. Moreover, these results obtained using different strains of A. fumigatus suggest that this 32-33-kDa serine proteinase is highly conserved in this pathogen.…”
Section: Fumigatus Various Enzyme Activities Were Charac-supporting
confidence: 88%
“…It has also been demonstrated that the prote01ytic activity in the brain of infected mice increases proportionally with the growth of A. fumigatus [3]. An extracellular alkaline protease (ALP), a serine protease of the subtilisin family, has been isolated from clinical sources of A. fumigatus [4][5][6]. This protease of 33 kDa was totally inhibited by PMSF, antipain, chymostatin, and /3-2-macroglobulin [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when cultivated in a medium containing human fibrinogen as sole nitrogen source, A fumigatus produced an extracellular fibrinogenolytic enzyme [7]. This exoprotease, which has been identified to be a chymotrypsin-like serine protease [24], degraded elastin [17,331 and collagen [30]. Its ability to detach Vero ceils in culture from plastic substrate or to induce the detachment of human epithelial cells from basement membrane was also reported [33, 341. Destruction of the extracellular matrix proteins could contribute to the pathogenesis of the disease [27,28].…”
Section: Introductionmentioning
confidence: 99%